Expresamos y controlamos nuestras emociones - Dedios Morales, Karina Elizabeth (2019)
The purpose of this Professional Sufiscience Work is to help students identify their emotions and know how to apply self-regulation strategies, when they need it throughout their lives. Emotions in Psychology are defined, as that feeling or perception of the elements and relationships of reality or imagination. There are basic emotions such as: joy, sadness, fear, anger, surprise and disgust or dislike. The session entitled Express and control our emotions, was developed in the area of Social Staff, taking into account the competence, Builds its identity, emphasizing the capacity, Self regulates its emotions and has achieved in students the performance, Describes its emotions, recognizes causes and consequences and applies self-regulatory strategies; third graders in primary education. In the course of the session, the development of motivating and challenging activities, which encouraged the active participation of students, was applied. The pedagogical processes of a session and the teaching processes of the area were taken into account, using the Valuation Scale as an evaluation tool.